Evaluation of the effect of different attachment configurations on molar teeth in maxillary expansion with clear aligners - a finite element analysis - Nurver Karslı; Irmak Ocak; Müge Akyıldız; Hakan Gögen; Oyku Dalci (BMC, 2024)
Abstract Objective To evaluate the effects of different attachment configurations with and without buccal root torque on expansion movements achieved with aligners through finite element analysis (FEA). Methods FEA modelling was done with 0.25 mm buccal expansion force application to the maxillary molars with different attachment configurations: Eight models were tested (1) no attachment (NA), (2) horizontal attachment (HA), (3) gingivally beveled horizontal attachment (GHA), and (4) occlusally beveled horizontal attachment (OHA), as well as models with 6obuccal root torque, (5) no attachment (TNA), (6) horizontal attachment (THA), (7) gingivally beveled horizontal attachment (TGHA), and (8) occlusally beveled horizontal attachment (TOHA). Results The first and second molars exhibited buccal tipping in all models. The highest amount of buccal tipping for the molars was observed in the NA (6CMB, 0.232 mm; 6CMP, 0.246 mm; 7CMB, 0.281 mm; 7CMP, 0.312 mm) and GHA (6CMB, 0.230; 6CMP, 0.245; 7CMB, 0.279 mm; 7CMP, 0.311 mm) models, respectively, while the least tipping was observed in the TOHA model (6CMB, 0.155 mm; 6CMP, 0.168 mm; 7CMB, 0.216 mm; 7CMP, 0.240 mm). In all groups, the buccal tipping of the second molars was higher than that of the first molars. Conclusion This FEA study showed that expansion with aligners tip maxillary molars buccally and the use of occlusally beveled attachments and addition of buccal root torque reduces uncontrolled buccal tipping.